Kikuchi — Fujimoto disease: cervical lymphadenopathy suggestive of relapsing lymphoma in patient with lymphoblastic lymphoma - Urun, Y.; Utkan, G.; Kankaya, D.; Dogan, M.; Yalcin, B.; Icli, F. (Experimental Oncology, 2011)
Aim: Kikuchi — Fujimoto disease (KFD) or histiocytic necrotizing lymphadenitis is a rare disorder and often confused with lymphoma. Patient: There is presented a case of 28-year-old patient with cervical lymphadenopathy, who had history of lymphoma. Results: On immunohistopathologic examination diagnosis of KFD was made and patient followed without any treatment. Conclusion: Patient’s lymphadenopathy had almost resolved and he was completely asymptomatic after three months. In patient with cervical lymphadenopathy KFD should be considered in the differential diagnosis.